Modul Digital Interaktif Berbasis Science Technology Engineering Mathematics (STEM) Pada Materi Energi Terbarukan - laila, Laila Nuraini Fitri; Vina Serevina; Ely Rismawati (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study aims to develop an interactive digital module based on STEM by utilizing the Canva and Heyzine Flipbooks platforms as supporting media. The benefits of this study are to contribute to the development of STEM-based learning concepts, especially in renewable energy materials. This research was conducted at SMA Negeri 59 Jakarta in the even semester of 2025. This research method used Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results of this study indicate that the developed product is declared very feasible to use, with an assessment from media experts of 89% (very feasible), material experts 86% (very feasible), and learning experts 96% (very feasible). The product trial results also showed a high level of feasibility, namely 96% (very good) from teachers and 85% (very good) from students. Thus, the interactive digital module based on STEM on renewable energy material is suitable for use as a physics teaching material in high school.